SISTEM INFORMASI PENGELOLAAN LOGISTIK BAHAN BANGUNAN BERBASIS WEB PADA PT MEDIA BERSAMA JAYA KONSTRUKSI - Aritonang, Ripka Elisabet Br; Terttiaavini; Ariati, Nining (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Web-based Building Material Logistics Management Information System is designed to improve efficiency in stock and logistics management at PT Media Bersama Jaya Konstruksi. This system aims to help companies monitor and manage building material inventory in real-time, track the ordering process to material delivery, and provide accurate material usage reports. In construction projects, good stock management is very important to avoid work delays due to lack of materials. With the implementation of this system, companies can optimize the use of resources, save time and operational costs, and improve transparency and accuracy of logistics data. This system is expected to be an effective solution in supporting the smooth running of construction projects as a whole.